Mechanisms of Macrophage Plasticity in the Tumor Environment: Manipulating Activation State to Improve Outcomes - Ricketts, Tiffany Davia; Prieto-Dominguez, Nestor; Gowda, Pramod Sreerama; Ubil, Eric (Frontiers in Immunology, 2021)
Macrophages are a specialized class of innate immune cells with multifaceted roles in modulation of the inflammatory response, homeostasis and wound healing. While developmentally derived or originating from circulating monocytes, naïve macrophages can adopt a spectrum of context-dependent activation states ranging from pro-inflammatory (classically activated, M1) to pro-wound healing (alternatively activated, M2). Tumors are known to exploit macrophage polarization state to foster a tumor-permissive milieu, particularly by skewing macrophages toward a pro-tumor (M2) phenotype. These pro-tumoral macrophages can support cancer progression by several mechanisms including immune suppression, growth factor production, promotion of angiogenesis and tissue remodeling. By preventing the adoption of this pro-tumor phenotype or reprogramming these macrophages to a more pro-inflammatory state, it may be possible to inhibit tumor growth. Here, we describe types of tumor-derived signaling that facilitate macrophage reprogramming, including paracrine signaling and activation of innate immune checkpoints. We also describe intervention strategies targeting macrophage plasticity to limit disease progression and address their implications in cancer chemo- and immunotherapy.